Social Realism And Historical Context In The Works Of John Steinbeck (Eurasian Journal of Humanities and Social Sciences, 2026)
Article explores the themes of social realism and historical context in the works of John Steinbeck, a prominent American author of the 20th century. It examines how Steinbeck's writing reflects the social issues and economic challenges faced by individuals and communities during the Great Depression and other significant historical events. Through an analysis of key texts such as "The Grapes of Wrath" and "Of Mice and Men," the article highlights Steinbeck's portrayal of the struggles of marginalized groups, including migrant workers and impoverished families. It also discusses how his characters embody the resilience of the human spirit amidst adversity, showcasing the interconnectedness of individual experiences and broader societal issues. By situating Steinbeck's work within its historical context, the article underscores the relevance of his themes to contemporary social justice movements and the enduring impact of his literary legacy